Augmented Reality Based Activities to Support Vocabulary Retention, Motivation, and Engagement in Language Learning - Umi Salamah; Yuni Eka Fajarwati; Mohammed Dawood Ansari (International Forum of Researchers and Lecturers, 2025)
This study investigates the effectiveness of Augmented Reality (AR) based activities in supporting vocabulary retention, motivation, and engagement in foreign language learning. A quasi-experimental design with a pre-test–post-test control group was employed, involving university students enrolled in English as a Foreign Language (EFL) courses. The experimental group engaged in AR-supported vocabulary learning, while the control group used conventional methods such as flashcards and text-based materials. Data were collected through vocabulary tests, motivation and engagement questionnaires, and classroom observations. The findings indicate that AR significantly enhanced vocabulary retention, with students in the experimental group outperforming those in the control group. AR also increased learners’ motivation by providing immersive and enjoyable learning experiences, and it fostered greater engagement as students actively interacted with digital media. These results support the integration of AR into language learning as an effective instructional approach that combines contextualization, interactivity, and gamification. The study contributes to the growing body of research on technology-enhanced learning and highlights the pedagogical potential of AR in modern language education.